2002
DOI: 10.1038/sj.bmt.1703567
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Griscelli syndrome with unrelated donor allogeneic hematopoietic stem cell transplantation

Abstract: Summary:Griscelli syndrome (GS) is a rare autosomal recessive disorder, characterized by pigmentary dilution of the skin and hair and in most patients by abnormal regulation of the immune system, which results in a syndrome of macrophage hyperactivation, known as hemophagocytic lymophohistiocytosis (HLH). Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative treatment available for genetically induced HLH. Few cases of successful HSCT from a compatible donor have been reported in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Only a few cases of successful aHSCT have been described previously. [9][10][11][12][13][14] Schmid et al 26 recently reported their experience with aHSCT for 10 patients with type 2 GS. At a medium follow-up of 3.4 years, the OS was 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few cases of successful aHSCT have been described previously. [9][10][11][12][13][14] Schmid et al 26 recently reported their experience with aHSCT for 10 patients with type 2 GS. At a medium follow-up of 3.4 years, the OS was 70%.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few cases of aHSCT in patients with GS have been reported. [9][10][11][12][13][14] Materials and methods Table 1. The median age at diagnosis was 6.8 (range, 0-17.2) months.…”
Section: Introductionmentioning
confidence: 99%
“…Griscelli and Prunieras 1 , in the first description of the syndrome, did not described any neurologic manifestations. Latter, many authors reported the presence of seizures, intracranial hypertension, hemiparesis, facial palsy, hypotonia, psychomotor and language delay, progressive neurologic deterioration, cerebellar signs and spasticity [4][5][6][7][8][9][10][11][12] . According to Malhotra et al 3 severe neurologic abnormalities are common in GS type 1 and may be absent in GS type 2.…”
Section: Discussionmentioning
confidence: 99%
“…The physiopathology of GS is based on a limited transport of melanin taking to a melanossoma deposition in the melanocytes 4 . Many of these cases were found in multiple siblings and/or consanguineous parents, suggesting an autossomal recessive inheritance 5,6 . In 1997, Pastural et al 7 found a homozygous mutation of the gene encoding myosin VA protein (MYO5A) in a Turkish girl with Griscelli syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation